Self-Consciousness of Tounsawang Women Ethnic in Individual, Family, and Social-Economic Empowerment in Southeast Minahasa, North Sulawesi - Treesje Imran; Mustain Mashud; Nurul Hartini (Journal of The Community Development in Asia, 2022)
This study aims to examine and analyze the Self-Consciousness of women from the Tounsawang Southeast Minahasa ethnic group in empowering themselves. The research problem is how Self Consciousness of Women in self-empowerment, Family empowerment, and Socio-Economic work. By using qualitative methods, the research was conducted in the sample areas named Betelen Village, Tombatu Satu and Tombatu Dua. The results of the study are 1. Women have very high awareness in empowering themselves because women interpret the principles of Si Tou Timou Tumou Tou as humans live to bring others to life. 2. Women empower their families by working hard and replacing their husbands in Mapalus work and also representing the family in various community activities. 3. Women are empowered in social and economic life to increase family income and welfare.